2013
DOI: 10.1680/wama.11.00095
|View full text |Cite
|
Sign up to set email alerts
|

Anfis to estimate discharge capacity of rectangular side weir

Abstract: The adaptive neuro-fuzzy inference system (Anfis) is considered for flow over rectangular side weirs located on a straight channel as a substantial part of distribution channels in irrigation systems and treatment units. To estimate the outflow over a rectangular sharp-crested side weir, the discharge coefficient in the side weir equation needs to be determined in accordance with the effective dimensionless parameters F1 (Froude number), L/b (weir length/channel width), L/h1 (weir length/flow depth), and p/h1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…ANFIS, introduced by Jang [28], is widely applied in various engineering problems up to now [29][30][31][32]. ANFIS is a combination of a fuzzy inference system and Artificial Neural Network (ANN).…”
Section: Anfis Methodsmentioning
confidence: 99%
“…ANFIS, introduced by Jang [28], is widely applied in various engineering problems up to now [29][30][31][32]. ANFIS is a combination of a fuzzy inference system and Artificial Neural Network (ANN).…”
Section: Anfis Methodsmentioning
confidence: 99%
“…Dursun et al (2012) applied ANFIS to predict the characteristics of semi-elliptical side weirs. Kisi et al (2013) simulated the discharge coefficient of rectangular side weirs using ANFIS and concluded that ANFIS performs much better…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that the historical time series have similar statistical parameters to those of the generated time series at 95% confidence level. Kisi et al (2013) used ANFIS approach and successfully modeled the discharge capacity of rectangular side weirs. Marsili-Libelli et al (2013) proposed a new stream flow assessment method based on fuzzy habitat suitability and large scale river modeling.…”
Section: Introductionmentioning
confidence: 99%